2023
DOI: 10.3390/su151612664
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Sustainability and Financial Performance: The Moderating Effect of CEO Characteristics

Abdulateif A. Almulhim,
Abdullah A. Aljughaiman

Abstract: This study aimed to investigate the effect of corporate sustainability on financial performance as well as examine whether CEO characteristics influence the association between corporate sustainability and the financial performance of listed firms in the Saudi Stock Exchange. In this vein, this study is the first to utilize multiple CEO characteristics as a moderating role influencing the association between corporate sustainability and financial performance. In addition, the study focuses on the developing co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…Huh et al (2022) [101] examined the structural relationship between ESG management, corporate reputation, and financial performance and found that all components of ESG management had a significant and positive impact on corporate reputation. Luan and Wang (2023) [102] However, Almulhim and Aljughaiman (2023) [104] revealed that firms with more ESG activities tend to have negative financial performance. In Yang et al [105], among ESG activity variables, only governance was found to have a significant negative impact on financial performance, and environmental and social variables were found to have no significant impact on financial or non-financial performance.…”
Section: Esg Managementmentioning
confidence: 99%
“…Huh et al (2022) [101] examined the structural relationship between ESG management, corporate reputation, and financial performance and found that all components of ESG management had a significant and positive impact on corporate reputation. Luan and Wang (2023) [102] However, Almulhim and Aljughaiman (2023) [104] revealed that firms with more ESG activities tend to have negative financial performance. In Yang et al [105], among ESG activity variables, only governance was found to have a significant negative impact on financial performance, and environmental and social variables were found to have no significant impact on financial or non-financial performance.…”
Section: Esg Managementmentioning
confidence: 99%
“…Overall, the theory suggests that the personal attributes of the top decisionmakers are enduring characteristics that reflect firm outcomes, e.g., financial and environmental performance, and corporate strategies and effectiveness. Notably, the literature has documented the essential roles of CEOs in shaping the sustainable and environmental strategies of firms, i.e., their environmental policies and practices [12,17,[34][35][36]. Furthermore, CEOs are also responsible for the deployment of the financial resources of firms, which can be distributed to implement long-term strategic environmental management [37].…”
Section: Ceos and Corporate Environmental Decisionsmentioning
confidence: 99%
“…A substantial amount of prior literature has reported the significant impacts of the CEO's age and educational background on a firm's corporate social responsibility in general and on environment-related matters in particular [8][9][10][11]. For instance, Almulhim and Aljughaiman [12] showed that CEO attributes, such as CEO gender, education, and tenure, influence the relationship between the environmental, social, and governance (ESG) level and corporate performance.…”
Section: Introductionmentioning
confidence: 99%
“…However, we used two criteria to filter our data. First, banks that have not provided governance or fintech data for a minimum of three years are dropped from our sample (Almulhim, 2023;Almulhim and Aljughaiman, 2023). Besides, banks that were merged during the study period were dropped from the sample (Almulhim, 2022).…”
Section: Data Samplementioning
confidence: 99%